Saliva Based Liquid Biopsies in Head and Neck Cancer: How Far Are We From the Clinic? - Patel, Aditi; Patel, Shanaya; Patel, Parina; Tanavde, Vivek (Frontiers in Oncology, 2022)
Head and neck cancer (HNC) remains to be a major cause of mortality worldwide because of confounding factors such as late-stage tumour diagnosis, locoregional aggressiveness and distant metastasis. The current standardized diagnostic regime for HNC is tissue biopsy which fails to determine the thorough tumour dynamics. Therefore, due to the ease of collection recent studies have focused on the utility of saliva based liquid biopsy approach for serial sampling, early diagnosis, prognosis, longitudinal monitoring of disease progression and treatment response in HNC patients. Saliva collection is convenient, non-invasive, and pain-free and offers repetitive sampling along with real time monitoring of the disease. Moreover, the detection, isolation and analysis of tumour-derived components such as Circulating Tumour Nucleic Acids (CTNAs), Extracellular Vesicles (EVs), Circulating Tumour Cells (CTCs) and metabolites from saliva can be used for genomic and proteomic examination of HNC patients. Although, these circulatory biomarkers have a wide range of applications in clinical settings, no validated data has yet been established for their usage in clinical practice for HNC. Although improvements in isolation and detection technologies and next-generation sequencing analysis have resolved many technological hurdles, allowing a wide range of saliva based liquid biopsy application in clinical backgrounds. Thus, in this review, we discussed the rationality of saliva as plausible biofluid and clinical sample for diagnosis, prognosis and therapeutics of HNC. We have described the molecular components of saliva that could mirror the diseases status, recent outcomes of salivaomics associated with HNC and current technologies which have the potential to improve the clinical value of saliva in HNC.